2015
DOI: 10.1515/bvip-2015-0075
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of modified therapeutic protocol in the treatment of some varieties of canine cardiovascular dirofilariasis

Abstract: The paper presents clinical diagnostic approaches and therapeutic effects of a specific protocol for the treatment of dogs with cardiovascular dirofilariasis in the Belgrade City (Serbia) territory. The study involved 50 privately owned dogs of different breeds, gender, and age, all showing signs of cardio -respiratory disorders. In addition to a general physical examination, blood tests were done to detect microfilaria and adult forms, and X-ray, ECG, and echocardiography were performed as well. At the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Melarsomine is not registered in Serbia, so alternative therapy consisting of doxycycline and ivermectin in different application regimes is widely used (Spasojević Kosić et al 2020;Milojković et al, 2016;Stepanović et al, 2015;Spasojević Kosić et al, 2014b;. We have been studying effects of alternative therapy consisting of doxycycline and ivermectin (Spasojević Kosić et al, 2020;2014b; in dogs naturally infected with D. immitis for ten years and have come to the conclusion that the majority of treated dogs have no mf after one month of the therapy, while all initially microfilariaemic dogs have no more mf after 90 days' therapy.…”
Section: Therapy Of Heartworm Diseasementioning
confidence: 99%
“…Melarsomine is not registered in Serbia, so alternative therapy consisting of doxycycline and ivermectin in different application regimes is widely used (Spasojević Kosić et al 2020;Milojković et al, 2016;Stepanović et al, 2015;Spasojević Kosić et al, 2014b;. We have been studying effects of alternative therapy consisting of doxycycline and ivermectin (Spasojević Kosić et al, 2020;2014b; in dogs naturally infected with D. immitis for ten years and have come to the conclusion that the majority of treated dogs have no mf after one month of the therapy, while all initially microfilariaemic dogs have no more mf after 90 days' therapy.…”
Section: Therapy Of Heartworm Diseasementioning
confidence: 99%
“…In Serbia, several studies related to the presence of zoonotic nematodes in wild carnivores (Ilić et al, 2016a;2016b;Hadži-Milić et al, 2016;Gajić et al, 2019), nonowner dogs (Ristić et al, 2020a;2020b), shelters dogs (Ilić et al, 2021), and owned dogs and cats (Ilić et al, 2017;Ristić et al, 2020a;Stepanović et al, 2021) have been reported, while those related to carnivorous filariasis are of special importance (Tasić et al, 2008;Tasić et al, 2012;Penezić et al, 2014;Stepanović et al, 2015;Gavrilović et al, 2015;Kurucz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%